Comparison of the Subchronic Anti-Inflammatory Activity of the Ethanol and Ethyl Acetate Extracts of Breadfruit Leaves (Artocarpus altilis) on CFA-Induced Mice - Widhihastuti, Endah; Ni'ma, Neli Syahida; Widyarini, Sitarina; Fakhrudin, Nanang (Universitas Negeri Semarang, 2021)
Chronic inflammation of the joints can cause rheumatoid arthritis (RA). Breadfruit (Artocarpus altilis) is known to have anti-inflammatory activity. Previous studies showed that ethanol and ethyl acetate extracts of breadfruit leaves have anti-inflammatory activity in an acute anti-inflammatory model. This study aimed to determine the sub chronic anti-inflammatory activity of the ethanol and ethyl acetate extracts in CFA-induced mice. Balp/c mice (15) were divided into 5 groups: normal group, solvent-treated group, diclofenac sodium-treated group (dose 3 mg/kgBW), ethyl acetate extract-treated group (500 mg/kgBW dose), and ethanol extract-treated group (500 mg/kgBW dose). The extracts were given orally every day for 28 days. The body weight and edema volume were measured on the day of 1, 7, 14, 21, and 28 after CFA induction. This study showed that the ethanol and ethyl acetate extracts were able to inhibit inflammatory process by reducing the edema in mice. Ethyl acetate extract exhibited a stronger anti-inflammatory activity compared to the ethanol extract. Although the body weight of the mice treated with the ethanol extract was higher than that of the ethyl acetate extract, both extracts did not cause a significant change in body weight compared to the normal group. The results of this study indicated that the ethanol and ethyl acetate extracts of breadfruit leaves both demonstrated a sub chronic anti-inflammatory activity in mice.